Teaching Writing To The Seventh Year Of Smp Bhakti Karya Mojogedang Karanganyar In 2011/2012 Academic Year - Jannah, M.Nurul (2012)
studentsof SMP Bhakti Karya in 2011/2012 academic year. The objectives of this research paper are to describe:1) process of teaching learning writing in the first year students in SMP Bhakti Karya Mojogedang. 2) techniques of teaching writing . 3. the problem in teaching learning writing The type of this research is descriptive qualitative research. The data of this research are collected by observing the English class and interviewing the English teacher. The data of this research are the seventhyear student‟s activities in writing in SMP Bhakti Karya Mojogedang in 2011/2012 academic year, field note and data from interviewing English teacher. The subject of this researchis English teacher and the seventh year students of SMP Bhakti Karya Mojogedang. The object of this research is teaching writing to the seventh year students in SMPBhakti Karya Mojogedang, .The methods of collecting the data of the research are observation, interview, and documents. Based on the result of the analysis, the teacher uses BKOF, MOT, JCOT, ICOT as the learning procedure. The procedures of teaching writing is developing and preparing the student‟s writing skill. The materials are students worksheet and real situation. The media are picture, and real condition. The techniques are classroom discusion, task and pairwork. The evaluation is conducted by interpreting all of English skills. While the teacher roles are as facilitator, councelor, and motivator. The teacher‟s problems are: teaching learning process and writing structure. The problem solving applied by the teacher in teaching writing are by using group work to manage the number of the students that overload ,arranging the position of the students place in class, giving advice, motivation, and uses interesting media to attract the students attention in English teaching learning process.